Synthesis and Biological Evaluation of Furanoallocolchicinoids; Journal of Medicinal Chemistry; Vol. 58, iss. 2 - Voitovich Y. V. Yuliya; Shegravina E. S. Ekaterina; Sitnikov N. S. Nikolay; Faerman V. I. Vladimir; Fokin V. V. Valery Valerjevich; Schmalz H.-G. Hans-Gunther; Combes S. Sebastien; Allegro D. Diane; Barbier P. Pascal; Beletskaya I. P. Irina; Svirshchevskaya E. V. Elena; Fedorov A. Yu. Alexey (2015, 2015)
Title screen